Pengaruh Media Dadu Kata Bergambar terhadap Kemampuan Membaca Permulaan Peserta Didik - Hasnah, Hasnah; Frasandy, Rendy Nugraha; Yuliantika, Sonya (Mitra PGMI: Jurnal Kependidikan MI, 2023)
The purpose of writing this research to determine the effect of pictorial word dice learning media to improve students' initial reading skills at SD IT. This type of research is a quasi-experimental. The population in this study were students of class III A and III B as many 46 students. Sampling was carried out using the Saturated Sampling technique, the class selected as the experimental class was III A and the control class was III B. Data collection techniques were carried out by observation, tests, questionnaires, and documentation. The data analysis technique was carried out by normality test, homogeneity test, and hypothesis testing using SPSS.The results showed that the average post-test score for the experimental class was 88.38%. Based on the hypothesis test with SPSS obtained a significant in two sides (2-tailed) of = 0.000, it can be concluded that (0.000 <0.05). Therefore, it can be said that H0 which reads that there is no effect of using pictorial word dice learning media to improve students' initial reading ability is rejected and Ha is accepted, which means that there is an effect of using pictorial word dice learning media to improve students' initial reading ability at SD IT.